Treatment of Postpartum Depression with Neurosteroids - Stankevičiūtė, Reda; Strumila, Robertas (Neurologijos seminarai, 2024)
Neurosteroids, such as allopregnanolone, are primarily synthesized substances in the central nervous system which influence processes occurring in the brain. Fluctuations in the levels of neurosteroids can result in an increased anxiety and heightened sensitivity. Significant reduction in neurosteroid synthesis usually occurs during the perimenstrual and postpartum periods when very low levels of progesterone are observed. It is believed that a lack of neurosteroids in the body is one of the main causes of postpartum depression. Postpartum depression (PPD) is a form of depression which develops in women during the postnatal period. Clinical studies have been conducted, and the results indicate that Brexanolone (a water-soluble formulation of allopregnanolone) is effective in treating postpartum depression. Based on the evaluation of the HAMD-17 depression scale, women with PGD who received injectable neurosteroid doses achieved remission from postpartum depression more effectively and quickly than those in the placebo group. Subsequent studies were also conducted with the tablet form of neurosteroids (Zuranolone), and the results similarly showed favorable outcomes for postpartum depression. Additionally, during treatment with both injectable and tablet forms of neurosteroids, there were relatively few and non-threatening side effects for patients. This suggests that the benefits of neurosteroids in treating PPD may outweigh the potential harm and should possibly be considered and incorporated into the European psychiatric practice.